Metallophthalocyanines in a ternary photoactive layer (P3HT:MPc:PC70BM) for bulk heterojunction solar cells. Issue 8 (7th November 2020) - Gounden, Denisha; Pillay, Michael N.; Raab, Timo; Nombona, Nolwazi; Schmidt-Mende, Lukas; van Zyl, Werner E.
Abstract : Novel bulk heterojunction organic photovoltaic solar cells have been fabricated by introducing a series of metallophthalocyanines into a photoactive blend of a poly(3-hexylthiophene-2, 5-diyl) and [6, 6]-phenyl C70 butyric acid methyl ester. Abstract : Novel bulk heterojunction (BHJ) organic photovoltaic (OPV) solar cells have been fabricated by introducing a series of metallophthalocyanines (MPcs) into a blend of a poly(3-hexylthiophene-2, 5-diyl) (P3HT) and [6, 6]-phenyl C70 butyric acid methyl ester (PC70 BM) photoactive layer. Sixteen MPcs have been synthesised with due consideration of the metal type and valency, functionalised ligand moieties and their respective molecular energy levels. The MPcs were expected to act as an electron cascade material that improves the photovoltaic performance in a two-fold manner: first, to provide an efficient energy level offset between the polymeric donor (P3HT) and the fullerene-based derivative acceptor (PC70 BM) to enhance charge transfer and reduce recombination within the OPV solar cells, and second, to harvest a greater portion of the solar spectrum as MPcs are associated with absorption near the near-infrared region. BHJ OSCs were fabricated in the following inverted configuration: ITO/TiO2 /P3HT:MPc:PC70 BM/WO3 /Ag and were investigated for their optimum photovoltaic performance. The BHJ OSCs comprising P3HT, PC70 BM and the manganese MPc (MnPc) series photoactive layer displayed the best PCEs in the range of 2.36–2.62% which were approximately 47.5–63.7% higher than those of the binary reference BHJ OSCs.